Integrated washland management for flood defence and biodiversity - Morris, Joe; Hess, Tim M.; Gowing, D. J.; Leeds-Harrison, Peter B.; Bannister, N.; Vivash, R. M.; Wade, M. (Cranfield University, 2003)
A combination of reform of agricultural policy, changing priorities in the countryside, growing commitment to protect and enhance biodiversity, and concerns about increased flood risk in lowlands have drawn attention to the potential contribution that managed washlands can make to deliver benefits to biodiversity and flood management. In this context, and with funding from Defra and English Nature, the study reported here1 set out to determine the scope for simultaneously achieving flood management and biodiversity objectives, and how this might be achieved in practice. The broad purpose is to inform policy on washland creation and management, including mechanisms for implementation if deemed appropriate.